Associational resistance to both insect and pathogen damage in mixed forests is modulated by tree neighbour identity and drought. (14th May 2020) - Field, Elsa; Castagneyrol, Bastien; Gibbs, Melanie; Jactel, Hervé; Barsoum, Nadia; Schönrogge, Karsten; Hector, Andrew
Abstract: Tree health declines can be caused by interactions between pests and pathogens and many studies have shown a reduction in their damage in mixed species forests compared to monocultures. Yet few authors have considered tree diversity effects on both groups simultaneously. Moreover, it is unclear whether diversity effects on tree pests and pathogens are robust to changes in abiotic conditions, such as drought. We addressed tree diversity effects on foliar insect herbivory, oak powdery mildew and their interaction under contrasting water regimes in a large-scale tree diversity experiment in SW France. Using an irrigation treatment that alleviated drought conditions, we were able to experimentally assess the effects of tree diversity under contrasting abiotic environments. We surveyed plots along a richness gradient from one to four tree species, in which a focal study species of oak ( Quercus robur ) was mixed with other oak species ( Q. pyrenaica and Q. ilex ) and a taller, broadleaved species ( Betula pendula ). Increasing tree species richness lowered leaf miner abundance, leaf chewer damage and oak powdery mildew infection, consistent with a protective effect of resource dilution. However, richness effects on leaf miners were stronger in irrigated compared to non-irrigated blocks, indicating that environmental conditions can modulate diversity effects. Separate from the effect of tree species richness, the presence of birch in a plot increased damage by leaf chewers and powdery mildew, but lowered leaf miner damage, suggesting additional tree neighbour identity effects potentially linked to modulation of microclimate. We found a negative association between leaf miner abundance and oak powdery mildew, consistent with antagonism between oak damage agents. Synthesis . Overall, our study illustrates the importance of considering both tree diversity and composition (neighbour identity) in designing forests more resistant to pest and pathogen damage. Abstract : This study from a large‐scale tree diversity in SW France investigates the simultaneous effects of tree diversity and drought on tree pest and disease damage. In addition to providing support for associational resistance in mixed forests to both insect herbivores and a specialist pathogen, we show that the identity of neighbouring species can impact upon associational effects. Moreover, we found that the effect of tree diversity on leaf miners was contingent on water availability, suggesting bottom‐up effects of water relations on tree growth that impacted associational effects.